SIFAT FISIK TANAH DI BAWAH TEGAKAN MANGROVE DI DESA TUMPAPA KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Mahmud, Mahmud; Wardah, Wardah; Toknok, Bau (Warta Rimba, 2014)
Mangrove forest grows on transition of land and sea area which plants community grow on salty tolerance. Naturally properties of mangrove soil can be a standard on asessing its potency and productivity. The aim of this research was to investigate the physical properties of mangrove forest soil.The usage ofÂ this research are to enrich knowledge about physical properties of mangrove forest soil and may be as an input on mangrove forest development. This research was conducted in mangrove forest of Tumpapa Village Balinggi District, Parigi Moutong Regency, as long as three months (September up to December 2013) by using descriptive method. Descriptive research is research that intends to create a description of situations or events in the field. The placement of sampling plots purposive sampling methode with one plot in each of mangrove forest zonation. Collected soil samples were analyzed of soil textures, colours, and permeabilities. This research results shown that the soil of zone that anytime flooded has dusty-clayey clay texture, upper layer has gray colour, bottom layer has black colour, and slow permeability; the soil of zone with moderate tide flooded has dusty clay texture, upper layer has black colour, bottom layer has brown colour, and moderate permeability; the soil of zone with high tide flooded has dusty clay texture, upper layer has brown colour, and moderate permeability; and soil of transition area has clay texture, upper layer has brown colour, sub layer has black colour, bottom layer has gray colour,and slow permeability. Keywords : Mangrove forest, physical soil properties, zonation